2006
DOI: 10.1007/s00467-006-0216-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of histologic changes in the urinary tract of hypercalciuric rats

Abstract: Idiopathic hypercalciuria (IH) has been speculated to have a predisposing role in the development of urinary tract infection (UTI), due to the uroepithelial cell damage it leads to. In this study, we aimed to investigate the effects of hypercalciuria on the bladder, ureters, and kidneys in rats with experimentally induced hypercalciuria.Normocalcemic hypercalciuria was induced by furosemide (60 mg/100 mL of drinking water) administration to 16-week-old male Wistar Albino rats for 14 days. Calciuria (calcium/cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…We observed a high incidence of UTI (32%) in patients with renal hypercalciuria, implicating IH might be a major contributing factor to UTI in children. In rat models, hypercalciuria significantly affected on the cell architecture of the uroepithelium and disruption of the epithelial barrier of the bladder, ureter and all kidney structures, especially on the proximal epithelial cells (15). Therefore, this complication should also be considered when managing patients with IH in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a high incidence of UTI (32%) in patients with renal hypercalciuria, implicating IH might be a major contributing factor to UTI in children. In rat models, hypercalciuria significantly affected on the cell architecture of the uroepithelium and disruption of the epithelial barrier of the bladder, ureter and all kidney structures, especially on the proximal epithelial cells (15). Therefore, this complication should also be considered when managing patients with IH in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Akil et al, showed that hypercalciuric rats revealed proliferation and apical cytoplasmic vacuole formation in transitional epithelial cells of bladder and ureter specimens, and also vacuolization of proximal and distal tubules, tubular degeneration, interstitial edema and vasodilatation of the kidney. [10] According to Vachvanichsanong et al, decreasing urinary calcium excretion was associated with decreased symptoms of dysfunctional voiding. [6] Kaminska et al, showed that treatment of preurolithiasis state could decrease the recurrence rate of UTI.…”
Section: Discussionmentioning
confidence: 97%
“…Different mechanisms have been shown as responsible mechanism for UTI, such as uroepithelial damage by calcium oxalate monohydrate, the balance between bacterial virulence and host resistance, an inflammatory response to lipopolysaccharide (LPS) and low urinary secretory IgA (sIgA). [10][11][12][13] Hypercalciuria can predispose patients to UTI due to uroepithelial damage. Akil et al, showed that hypercalciuric rats revealed proliferation and apical cytoplasmic vacuole formation in transitional epithelial cells of bladder and ureter specimens, and also vacuolization of proximal and distal tubules, tubular degeneration, interstitial edema and vasodilatation of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent study shows that hypercalciuria has adverse effect on cell architecture of the uroepithelium and disruption of the epithelial barrier of the bladder and ureters and all kidney structures, especially on the proximal epithelial cells in hypercalciuric rats. 3 Taken together, these observations suggest that hypercalciuria maybe exert multiple functions in the kidney stone formation.…”
Section: Introductionmentioning
confidence: 91%